Realism In Naguib Mahfouz’s Literary Thought - Mohammad Sayedul Alam (al-Afkar, Journal For Islamic Studies, 2023)
Naguib Mahfouz (1911 – 2006) was an Egyptian writer who won the 1988 Nobel Prize in Literature. He is not only Egyptian but also Arab ever to be awarded the Nobel Prize for Literature. He published 35 novels, over 350 short stories. Mahfouz's literature is classified as realist  Literature, existential themes appear in it.  Mahfouz's novels published between 1945 and 1957 are generally realistic in content. Among these novels are 'Khan-al-Khalili' (1945), 'Al-Qahira al-Jadida' (1945) ('Cairo Modern'), 'Zukaq-al-Midaq' ('Midaq Alley') (1947), ' Al-Sarab' (1948) ('The Mirage'), 'Bidaya wa Nihaya' (1949) ('The Beginning and the End') and 'Thulathia-al-Qahira' (1956-1957) ('Cairo Trilogy') or 'Al-thulasia' ' ('Trio') is particularly famous. About 10 of his books were published before the Egyptian revolution organized on July 23, 1952. His writings played a special role in the intellectual organization of this revolution. Naguib Mahfouz wrote a number of short stories in the first decade of his literary career, and most of them dealt with the darker aspects of civic life. Many of the characters in Mahfouz's stories are taken directly from life. As a result, he quickly won the hearts of the readers. So, this research will contribute to enrich Arabic and world literatures.